Development of an alcoholic beverage based on sweet cucumber (Solanum Muricatum), for application in cocktails - Gamarra-Benites, Sonia Elizabeth; Rodríguez-López, Adriana Estefanía; Silva-Gómez, Efrén Alfredo (Ingeniería Química y Desarrollo, 2022)
The present work is focused on the alcoholic fermentation of sweet cucumber (Solanum Muricatum) for its subsequent implementation in the cocktail bar. Based on the foregoing, bibliographic studies were carried out to obtain information that supports the creation of the three experimental designs developed, by means of a quantitative methodology; had a fermentation time of twenty days, measuring pH, temperature, Brix degrees and their alcoholic content. The results achieved were led to an analysis of the aromatic profile of attributes, which gave the effect that their correct temperature ranges between 14 and 16 ° C, highlighting citrus and fruit aromas, greatly facilitating combinations of the realization of the cocktails, which were subjected to a hedonic test, concluding that the product with greater acceptability is the cocktail by direct method of tree tomato and grape.
Keywords: Fermentation; Solanum Muricatum; Experimentation; Aromatic Profile; Cocktails